PELATIHAN WIRAUSAHA PETANI MUDA MELALUI BUDIDAYA HIDROPONIK SISTEM WICK DAN NFT UNTUK MENDUKUNG PEMBANGUNAN DESA BERKELANJUTAN BERBASIS POTENSI DESA - Puspaningrum, Diah; Putri, Widya Kristiyanti; Aji, Joni Murti Mulyo; Subekti, Sri; Novikarumsari, Nurul Dwi; Patricia, Susan Barbara (INTEGRITAS : Jurnal Pengabdian, 2024)
Suci Village, Panti District, is one of the villages fostered by Jember University which has very good agricultural potential. The young generation of the village needs to be given education and mentoring to become more familiar with the concept of modern agriculture and realize it in cultivation and entrepreneurship practices. The community service in Suci Village aims to train the Karang Taruna "Tunas Muda" youth to cultivate and become hydroponic vegetable entrepreneurs using the wick and NFT systems. The stages of community service include education, installation construction, cultivation practice, and evaluation. Community service is carried out for 5 months. The results of this community service are that the youth of Suci Village who are members of the training know about cultivating and becoming entrepreneurs of hydroponic vegetable products. It is hoped that this community service will be able to increase village food security and support sustainable village development.